Pertimbangan Hakim Memutus Perkara Dengan Dissenting Opinion dalam Tindak Pidana Menelantarkan Isteri dan Anak - Wigit Mayang Panuluh (Verstek, 2019)
This writing aims to determine the consideration of the Supreme Court Justices impose the criminal punishment of the perpetrators of the crime of neglect of others in the household sphere. The research method used is normative legal research. The approach used is the approach of the Act and the case approach. Sources of legal materials used are primary and secondary legal materials. Based on the result of the research, it is known that the consideration of the Supreme Court Justices imposed the prison sentence in the criminal act of abandoning the wife and the child by dissenting opinion dissenting opinion (in this case one of the judges believes that the deed has not suffciently fulflled the criterion of a crime) in accordance with the provisions of Article 188 paragraph (4) jo of Article 243 of Law Number 31 of 1997 concerning Military Courts, which states that the decision in a deliberation is the result of a unanimous conspiracy, unless it has been sought after earnestly unreachable, the Decision shall be made by majority vote and if The Supreme Court granted the Supreme Court’s appeal, then the Supreme Court will revoke the Cassation’s decision. This is evidenced by the implementation of consensus deliberations in making decisions but not reached an agreement then the Panel of Judges make decisions based on the majority vote. The different opinions of the Judges are contained in the Supreme Court ruling. The Supreme Court granted the request of the High Military Oditur Case I Medan by canceling the High Court Military Court’s Decision of Medan. Declare the defendant guilty of committing a criminal act of abandoning another person in the household sphere and the Panel of Judges imposing a prison sentence on behalf of Defendant Riwanto for 4 (four) months.Keywords : neglect of people, judge’s consideration, dissenting opin